(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Reading English books plays a critical role in developing language skills among learners. It enhances vocabulary, comprehension, critical thinking, and overall communication abilities. This study explores the effects of reading English literature on language proficiency, focusing on primary and secondary learners. The research employs a qualitative approach, examining pedagogical strategies, reading habits, and learner outcomes. Findings reveal that consistent engagement with English texts significantly improves linguistic skills, reading comprehension, and expressive capabilities. The study emphasizes the importance of integrating book reading into language curricula to foster better communication and literacy.